1996
DOI: 10.1111/j.1744-313x.1996.tb00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Complement Third Component (C3) and Properdin Factor (Bf) Phenotypes in Patients With Various Clinical Manifestations of HBV Infection

Abstract: Four groups of children were tested for the distribution of C3 and BF phenotypes: HBV-infected patients with Gianotti-Crosti syndrome, with CAH and with glomerulonephritis, and healthy children. The frequency of the phenotype C3F was significantly higher in children with Gianotti-Crosti syndrome in comparison with healthy children. The frequency of the phenotype BFS was significantly higher in patients with glomerulonephritis than in individuals with CAH. The difference between the frequency of the BFS phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Immune complexes targeting hepatitis B surface antigen are considered to cause immune reactions that result in the skin lesions in GCS (22). Additionally, a study described cutaneous changes with itching following IFN administration to treat HBV infection or hepatitis B vaccination (23).…”
Section: Discussionmentioning
confidence: 99%
“…Immune complexes targeting hepatitis B surface antigen are considered to cause immune reactions that result in the skin lesions in GCS (22). Additionally, a study described cutaneous changes with itching following IFN administration to treat HBV infection or hepatitis B vaccination (23).…”
Section: Discussionmentioning
confidence: 99%
“…Further, several studies have indicated the participation of immunological mechanisms, such as the formation of immune complex (11,12).…”
Section: Discussionmentioning
confidence: 99%